Dependent development and regional integration : a critical examination of the Southern Cone Common Market - Richards, Donald G. (1997)
Examines the political-economic context in which the MERCOSUR has evolved to date so as to come to an understanding of its specific historical motivation, its objectives, and its likely consequences.